Attitudes towards mental illness and their effects on barriers in seeking psychological help: A study from the perspective of indigenous university students in Sabah - Getrude C. Ah Gang; Eric Manuel Torres; Lua Pei Lin; Kok Ann Gie (ResearchGate, 2024)
The mental health programs/campaigns organized by the relevant authorities can help elevate awareness among Indigenous students’ attitudes towards seeking psychological support. It is assumed that attitude towards mental illness can affect their interest in gaining psychological support when experiencing distress and depression. To explore this phenomenon, 87 Indigenous students in Sabah were involved in this study. Participants were selected via a random sampling of readily available and willing students. Data was collected using Google Formslinks and faceto-face surveys. The data was then analyzed using descriptive and inferential analysis. This study aimed to examine students’ attitudes towards mental illness and its impact on barriers to seeking psychological support. Based on a simple regression analysis, the study found that students’ attitudes had no significant effect on obstacles to seeking psychological help. However, students’ attitudes showed notable negative effects on one barrier component (i.e., perceived devaluation). The attitudes towards mental illness contributed 8.2 percent of the variance in perceived devaluation. This indicates that Indigenous students who showed more positive attitudes towards mental illness tended to demonstrate less perceived devaluation in seeking psychological help (e.g., they disagreed that their self-confidence might decrease if they sought psychological support from a professional). These positive attitudes likely derive from mental health programs/campaigns organized by universities and relevant organizations. Indeed, highlighting the importance of fostering positive mental health awareness for Indigenous university students may help to reduce the impediments to students seeking psychological help.